An approach to optimize process parameter for peptides extraction from Zophobas morio (Fabricius) using antifungal activity as the response - Faruck, Mohammad Omer; Yusof, Faridah; Chowdhury, Silvia (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Antifungal peptides have been successfully extracted from whole body larvae of Zophobas morio (Fabricius) by using acidified isopropanol. To ensure that the extraction is cost effective for maximum yield, Response Surface Methodology (RSM) using a Central Composite Design (CCD) strategy was adopted to optimize the extraction process parameters. The effect of independent parameters, namely, the homogenization temperature (°C), homogenization time (min) and solid (g) to solvent (ml) ratio of the extraction process on the fungal growth was studied. The extracted samples showed varying degree of antifungal activity against Aspergillus niger, the selected fungal strain, by using poisoned agar assay technique. Response surface investigation showed that the optimum values of the extraction parameters for antifungal peptides were 5 minutes homogenization time, 4°C homogenization temperature and 3.5:1 solid to solvent ratio. This study reports the development of an extraction process that allows careful recovery of antifungal peptides from insect larvae. In the validation of the experimental model, the error between the actual value and the predicted value was determined to be 3.54%.